Development of Sustainable Lean Patient Value in Healthcare: A Long-Term Condition Context. (3rd October 2022) - McAdam, Rodney; Galbraith, Brendan; McComb, Stephen; Antony, Jiju; Vijaya Sunder, M.
Abstract : The purpose of this paper is to examine the role of sustainable Lean patient value in relation to a long-term health condition in a healthcare context. A pragmatist research philosophy is used to conduct exploratory research utilising open data sources, semi-structured interviews, focus group meetings and participant workshops, where the quantitative data covered a 60-month period and the qualitative data collection and analysis covered a 36-month period. The findings show that Lean healthcare is overly focused on healthcare providers rather than patients leading to unmet value across the patient Value Stream. To conceptualise the findings and present the constructs and their relationships, a Lean patient healthcare framework is inductively developed. A number of propositions are advanced based on the relationships in the framework which provide a basis for further exploring improved Lean healthcare interventions in long-term conditions. The findings will assist healthcare academics, professionals and patient groupings in developing and improving Lean patient Value understanding and decision making. This will assist in effective Lean patient value creation and development for healthcare reforms and changes and in effective resource utilisation for improved and sustainable patient outcomes.